Model-Based Safety and Assessment : 6th International Symposium, IMBSA 2019, Thessaloniki, Greece, October 16-18, 2019, Proceedings /: 6th International Symposium, IMBSA 2019, Thessaloniki, Greece, October 16-18, 2019, Proceedings. (2019) - Unknown
No abstract available